2011
DOI: 10.1007/s00421-011-2000-6
|View full text |Cite
|
Sign up to set email alerts
|

Carbohydrate supplementation delays DNA damage in elite runners during intensive microcycle training

Abstract: The aim of this study was to evaluate the effect of carbohydrate supplementation on free plasma DNA and conventional markers of training and tissue damage in long-distance runners undergoing an overload training program. Twenty-four male runners were randomly assigned to two groups (CHO group and control group). The participants were submitted to an overload training program (days 1-8), followed by a high-intensity intermittent running protocol (10 × 800 m) on day 9. The runners received maltodextrin solution … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 44 publications
0
18
0
Order By: Relevance
“…Carbohydrate intake improves endurance performance 2%–6%, lowers perceived exertion, and attenuates post-exercise inflammation 25%–40% [3,4,5,6]. The consumption of multiple transportable carbohydrates (e.g., a mixture of glucose and fructose) during exercise improves the rate of carbohydrate oxidation [7], due to absorption of the carbohydrates by multiple transporters including the sodium-glucose transporter 1 (SGLT1), the universal glucose and fructose transporter (GLUT2), and the fructose transporter (GLUT5) [8].…”
Section: Introductionmentioning
confidence: 99%
“…Carbohydrate intake improves endurance performance 2%–6%, lowers perceived exertion, and attenuates post-exercise inflammation 25%–40% [3,4,5,6]. The consumption of multiple transportable carbohydrates (e.g., a mixture of glucose and fructose) during exercise improves the rate of carbohydrate oxidation [7], due to absorption of the carbohydrates by multiple transporters including the sodium-glucose transporter 1 (SGLT1), the universal glucose and fructose transporter (GLUT2), and the fructose transporter (GLUT5) [8].…”
Section: Introductionmentioning
confidence: 99%
“…However, few investigations of cf-DNA, as it relates to exercise and/or training, have been conducted. Recent studies of cf-DNA have explored the acute response of cf-DNA after a single bout of exercise [12][13][14][15][16][17] , as well as chronic changes in cf-DNA concentrations with resistance training 18 . These initial inquiries of post-exercise cf-DNA concentrations and training have suggested that cf-DNA may provide benefits over other markers of tissue damage and inflammation such as creatine kinase (CK) and C-reactive protein (CRP), for inclusion in a LTAMP.…”
Section: Introductionmentioning
confidence: 99%
“…With regard to effects of carbohydrate supplementation on oxidative DNA damage after exercise training, de Sousa et al (2011) have recently reported that ingestion of a carbohydrate beverage resulted in less DNA damage and attenuated the acute post-exercise inflammation response, providing better recovery during training. While carbohydrate supplementation in the present study were used to maintain an euglycemic state during exercise, whether it could be effective in attenuating the marked increase of exercise-induced DNA oxidation and consequently reducing disturbances at muscle and whole body levels cannot be concluded.…”
Section: Discussionmentioning
confidence: 99%